Supply Chain Business Intelligence Model for Quality Assurance in Educational Management for ASEAN University Network Quality Assurance - Chansamut, Artaphon (International Journal of Supply Chain Management, 2021)
This research was conducted to study and develop supply chain business intelligence model for quality assurance in educational management  for ASEAN University Network Quality Assurance (AUN-QA).The objective of this study  were  to study and evaluate supply chain business intelligence model for quality assurance in educational management  for ASEAN University Network Quality Assurance (AUN-QA). The research methodology consists of study, analyze, and synthesize the contents, develop a proces supply chain business intelligence model for quality assurance in educational management  for ASEAN University Network Quality Assurance (AUN-QA), present the constructed model, conclude the results and analyse the model’s results evaluation by using mean and standard and deviation .The fiveteen experts selected by purposive sampling. The data were analyzed by standard deviations and means.  The model development process has  five components: main component and Minor ingredients namely Suppliers, University manufacture, Customers and  Consumer. This model helps  to support sustainable business intelligence development As, the overall model was shown at a very good level, the experts agreed.